StonePT – Certification Trust and Quality Excellence of Portuguese Dimension Stones - Lopes, Luís (2018)
The main objective of the StonePT – Portuguese Stone Brand, is to certify the Natural Stone product, so that StonePT companies can technically communicate their products, with customers and prescribers, being easily identified through its BRAND, its Identity – StonePT. The StonePT brand is supported by a certification system, aiming at the international recognition of Portuguese natural stone construction products, not only for its physical and mechanical characteristics, but also for the Portuguese transformer knowledge. This certification system, based on technical specifications and harmonized European standards for construction products using natural stone, aims at fulfilling a market gap with regard to guarantee of origin and quality assurance associated with the processing and , not least, the suitability of using each type of stone for different applications. The advantages of using STONEPT brand by the companies could be listed as follows: a) Increases customer acceptance of products; b) Makes the difference compared to competitors; c) Increases competitiveness by reducing the costs of non-quality; d) Reinforces the image of the company; e) Facilitates access to new markets and, f) Allows to demonstrate compliance with regulatory requirements.